Prevalence and characteristics of gonadoblastoma in a retrospective multi-center study with follow-up investigations of 70 patients with Turner syndrome and a 45, X/46, XY karyotype. Issue 6 (24th November 2022) - Karila, Daphné; Donadille, Bruno; Léger, Juliane; Bouvattier, Claire; Bachelot, Anne; Kerlan, Veronique; Catteau-Jonard, Sophie; Salenave, Sylvie; Albarel, Frédérique; Briet, Claire; Coutant, Regis; Brac De La Perriere, Aude; et al.
Abstract: Introduction: A gonadectomy is currently recommended in patients with Turner syndrome (TS) and a 45, X/46, XY karyotype, due to a potential risk of gonadoblastoma (GB). However, the quality of evidence behind this recommendation is low. Objective: This study aimed to evaluate the prevalence of GB, its characteristics, as well as its risk factors, according to the type of Y chromosomal material in the karyotype. Methods: Our study within French rare disease centers included patients with TS and a 45, X/46, XY karyotype, without ambiguity of external genitalia. Clinical characteristics of the patients, their age at gonadectomy, and gonadal histology were recorded. The regions of the Y chromosome, the presence of TSPY regions, and the percentage of 45, X/46, XY mosaicism were evaluated. Results: A total of 70 patients were recruited, with a median age of 29.5 years (21.0–36.0) at the end of follow-up. Fifty-eight patients had a gonadectomy, at a mean age of 15 ± 8 years. GB was present in nine cases. Two were malignant, which were discovered at the age of 14 and 32 years, without metastases. Neither the percentage of XY cells within the 45, X/46, XY mosaicism nor the number of TSPY copies was statistically different in patients with or without GB ( P = 0.37). However, the entire Y chromosome was frequent in patients with GB (6/9). Conclusions: In our study, including a large number of patients with 45, X/46, XY TS, the prevalence of gonadoblastoma is 12.8%. An entire Y chromosome appears as the main risk factor of GB and should favor early gonadectomy. Significant statement: About 10% of patients with TS have a karyotype containing Y chromosomal material: 45, X/46, XY. Its presence is related to the risk of GB. Therefore, a prophylactic gonadectomy is currently recommended in such patients. However, the quality of evidence is low. Our objective was to evaluate the prevalence of GB according to the type of Y-chromosomal material. We found a prevalence of GB of 12.8% in a cohort of 70 TS patients. No sign of hyperandrogenism was observed. The entire Y chromosome was the most frequent type of Y-material in patients with GB. As the prognosis of these tumors was good, a delay of surgery might be discussed.